EVALUASI KERASIONALAN PENGOBATAN DIABETES MELITUS TIPE 2 PADA PASIEN RAWAT INAP DI RSUP PROF. DR. R. D. KANDOU MANADO TAHUN 2013 - Hongdiyanto, Arnold (PHARMACON, 2014)
This study aimed to evaluating the rational of in patients Diabetes Mellitus type 2 medication in RSUP Prof. dr. R.D. Kandou Manado at 2013. This study was conducted on 46 medical record of patients of Diabetes Mellitus type 2. The result showed that 46 in patient Diabetes Mellitus type 2 in RSUP Prof. dr. R.D. Kandou Manado at 2013 were 51-60 years old (58,7%). Diabetes Mellitus type 2 patients comprised 16 men and 30 women. 15 cases (32,6%) were Diabetes Mellitus type 2 without complication diseases and 31 cases (67,4%) Diabetes Mellitus type 2 with complication diseases. Patients had indication appropriate were 40 patients (86,96%), drug choise appropriate 40 patients (100%). Dosis appropriate were 36 patients (97,32%), patient appropriate were 40 patients (100%), while for drug interaction not interaction. Key words : Rational evaluation, Diabetes Mellitus type 2, RSUP Prof. dr. R.D. Kandou Manado